8 - Farewell Messages to Professor Adebayo Olukoshi, Executive Secretary of CODESRIA (2000–2008) 31 March 2009 - Mahmood Mamdani, (CODESRIA Bulletin, 2009)
Farewell Messages to Professor Adebayo Olukoshi, Executive Secretary of CODESRIA (2000–2008) 31 March 2009